Urgensi Perlindungan Hukum terhadap Para Pihak dalam Sengketa Wanprestasi Jual Beli Tanah (Tinjauan terhadap Putusan Nomor: 222/Pdt.G/2024/PN Tjk) - Ahmad Farhan Nindya Praja; Rifandy Ritonga (Lembaga Yasin AlSys, 2025)
This study is motivated by the high frequency of land sale and purchase agreements in Indonesian society, which often lead to disputes arising from wanprestasi—a breach of contractual obligations by one of the parties. Such conditions result in losses, legal uncertainty, and the potential for civil legal conflict. The objective of this research is to analyze the urgency of legal protection for parties involved in wanprestasi disputes over land sale agreements, with a specific focus on the decision of the Tanjungkarang District Court No: 222/Pdt.G/2024/PN Tjk, based on a case in Bandar Lampung. The study employs an empirical juridical method, combining normative legal analysis of legislation with empirical examination through court decision analysis and interviews with relevant stakeholders. The findings show that the judge provided thorough legal reasoning by declaring the defendant in wanprestasi and ordering restitution of rights to the plaintiff. The legal protection granted was not only declaratory but also executory, reflecting the law’s function as a concrete instrument for safeguarding civil rights. The study affirms the importance of a legal system that ensures justice and legal certainty in land transactions, which are vital to the economic and social interests of society. The implications of these findings highlight the need to raise public awareness regarding the legality of land sale agreements and to strengthen the role of legal authorities in upholding justice and the rule of law.